Research hotspots and frontiers of endoplasmic reticulum in glomerular podocytes: a bibliometric and visual analysis from 2005 to 2023 - Junli, Wang; Zhihong, Hao; Lina, Wang; Qiaoqun, Ou; Jing, Qu; Jiaqi, Hu; Yu, Shengyou (Frontiers in Pharmacology, 2025)
BackgroundThe glomerular podocyte endoplasmic reticulum is a critical component in renal function, yet its research landscape is not fully understood. This study aims to map the existing research on podocyte endoplasmic reticulum by analyzing publications in the Web of Science Core Collection (WOSCC) from the past 19 years.MethodsWe conducted a bibliometric analysis using Citespace, VOSviewer, the Metrology Literature Online platform, and the Bibliometrix software package to visualize and interpret the data from WOSCC. The analysis focused on publication volume, authorship, institutional contributions, and research trends.ResultsThe analysis revealed a significant growth in publications, indicating a surge in interest in podocyte endoplasmic reticulum research. Cybulsky, Andrey V, and Papillon, Joan emerge as the most prolific authors, and the Journal of the American Society of Nephrology is the leading journal in this field. China is the top contributor in terms of publications, with McGill University being the most productive institution. The research primarily focuses on endoplasmic reticulum stress, diabetic nephropathy, and apoptosis, with emerging trends in “foot cell apoptosis,” “cell signaling pathways,” and “autophagy.”ConclusionThe findings highlight the expanding scope of podocyte endoplasmic reticulum research, with a particular emphasis on the mechanisms of endoplasmic reticulum stress and podocyte apoptosis. Future research directions may include the identification of specific therapeutic targets, detailed exploration of podocyte signaling pathways, and the role of autophagy. This study provides a comprehensive overview of the major research areas, frontiers, and trends in podocyte endoplasmic reticulum research, which are pivotal for guiding future investigations.